2015
DOI: 10.1007/s00216-015-9025-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of non-traditional stable isotopes in analytical ecogeochemistry assessed by MC ICP-MS - A critical review

Abstract: Analytical ecogeochemistry is an evolving scientific field dedicated to the development of analytical methods and tools and their application to ecological questions. Traditional stable isotopic systems have been widely explored and have undergone continuous development during the last century.The variations of the isotopic composition of light elements (H, O, N, C and S) have provided the foundation of stable isotope analysis followed by the analysis of traditional geochemical isotope tracers (e.g. Pb, Sr, Nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 164 publications
0
36
0
Order By: Relevance
“…The modified high sensitivity sample and skimmer cones used in ICP‐MS have significantly improved the analytical sensitivity but also altered the instrumental mass discrimination behavior. Several studies have investigated the effects of different combinations of sample and skimmer cones on the extraction efficiency of plasma ions and mass discrimination behaviors using ICP‐MS and MC‐ICP‐MS . These studies indicated that the cone geometry that was expected to yield higher signal sensitivity in wet plasma mode (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified high sensitivity sample and skimmer cones used in ICP‐MS have significantly improved the analytical sensitivity but also altered the instrumental mass discrimination behavior. Several studies have investigated the effects of different combinations of sample and skimmer cones on the extraction efficiency of plasma ions and mass discrimination behaviors using ICP‐MS and MC‐ICP‐MS . These studies indicated that the cone geometry that was expected to yield higher signal sensitivity in wet plasma mode (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…10,30,34,35 The modified high sensitivity sample and skimmer cones used in ICP-MS have significantly improved the analytical sensitivity but also altered the instrumental mass discrimination behavior. Several studies have investigated the effects of different combinations of sample and skimmer cones on the extraction efficiency of plasma ions and mass discrimination behaviors using ICP-MS and MC-ICP-MS. [36][37][38][39] These studies indicated that the cone geometry that was expected to yield higher signal sensitivity in wet plasma mode (i.e. solution mode) [38][39][40][41] does not provide this for all elements by MC-ICP-MS. For example, a 30% decrease in signal intensity for Li and Mg isotopes and an increase in the signal intensity for Sr, Nd, Hf, Pb, and U isotopes were observed.…”
mentioning
confidence: 99%
“…Multi‐collector inductively coupled plasma mass spectrometry (MC‐ICP‐MS) has been widely used to measure metal stable isotopic compositions in recent decades (e.g …”
Section: Introductionmentioning
confidence: 99%
“…Review papers have been published in 2004 on the biological role of strontium [1] and in 2006 on the biogeochemistry of strontium [6]. From to 2005 to present several reviews including, but not exclusively, strontium isotopic analysis can be found in the literature, focused on different subjects, such as geochemistry, ecogeochemistry and archaeology [25][26][27] as well as analytical methodologies [28][29][30]. Food authentication presents itself as the application with most review papers on the subject of stable isotopic techniques.…”
Section: General Considerationsmentioning
confidence: 99%